"Fake Happiness": Counseling, Potentiality, and Psycho‐Politics in China. (8th October 2013) - Yang, Jie
Abstract: In China, an emerging psycho‐politics seeks to extract value from and to govern the potential of individual citizens. The party state attempts to preempt social unrest by encouraging the poor and the unemployed to engage in psychological self‐help to unlock their positive potential. Television counseling programs promoting the cultivation of happiness are part of these attempts. These programs showcase marginalized people who appear happy despite their limited life circumstances. Expert counselors glorify individuals who have actualized their potential through happiness to become entrepreneurs and role models. However, critics argue that these programs promote "fake happiness" and divert people's attention from structural forces that negatively affect their lives. This article advances these critiques by illustrating how happiness promotion in China taps into the resources of the victims of socioeconomic dislocation to effect economic advancement and political equilibrium. This article contributes to the growing anthropological literature on happiness by engaging happiness as a governing technology based on psychologization and as a force for both the government and underprivileged people to rally resources for their respective causes.